Material Characteristics and Electrical Performance of Perovskite Solar Cells with Different Carbon-Based Electrodes Mixed with CuSCN - Elang Barruna; Atya Saniah; Siti Fauziyah Rahman; Nji Raden Poespawati (Journal of Electrical and Computer Engineering)
Perovskite solar cells are the most cutting-edge photovoltaic technology having high efficiency and short fabrication time. In recent decades, there has been a significant rise in the study of the usage of carbon materials in perovskite solar cells because of low cost and earth abundance. Several studies have been conducted to mix hole transport materials with carbon materials to improve the hole extraction capability. Nevertheless, no research has reported using CuSCN on different carbon electrodes on perovskite solar cells. In this research, various carbon materials, including carbon nanotubes (CNT), graphite, activated carbon, and reduced graphene oxide (rGO), are mixed with CuSCN. The carbon materials and CuSCN were mixed by ball mill and then deposited using the doctor blading method to become an electrode layer. The existence of CuSCN in carbon materials was proved by conducting the energy dispersive X-ray test. CNT mixed with CuSCN material exhibits the highest electrical conductivity indicated by ID/IG ratio of 1.22 using Raman spectroscopy. Perovskite solar cell with a mix of CNT and CuSCN electrode exhibits the lowest series resistance of 76.69 Ω, resulting in the optimum solar cell performance such as a short-circuit current density (JSC) of 0.199 mA/cm2, open-circuit voltage (VOC) of 0.52 V, fill-factor (FF) of 0.369, and efficiency of 0.0735.